Pembelajaran Interdisipliner: Upaya Mengapresiasi Sastra Secara Holistik - Daru Kabeka Janarto (Bina Nusantara University, 2010)
The research is regarding 4 class cycle about interdisciplinary teaching technique of literature teaching in BINUS International School Simprug, Jakarta. The interdisplinary teaching is done in grade 10 in 3 subjects of Indonesian Language and Literature, Computer (IT), and Visual Arts. The teaching topic is Ma Yan, a novel about Muslim teenager who struggles for education in Zhang Jiashu, a remote village in China. This teaching climax is talk show with the writer of Ma Yan and its publisher followed with visual arts show from the students. The observation result shows that talent and involvement of students are high through the learning materials, proved by assignments done in time and their antusiasm towards their projects and assignments.